Essai de formulation d'un insecticide àbase d'huiles essentielles - BOUKHALFA, Radia; MERABET, Khemissa (جامعة الوادي - university of eloued, 2023)
Pesticides from stored food pests present a source of contamination of the food chain by toxic products. The objective of this study is to evaluate the toxic effect (inhalation and by contact) and the repellent effect of four essential oils: peppermint (Mentha ×piperita), clove (Syzygium aromaticum), basil (Ocimum basilicum) and lemongrass (Cymbopogon citratus), Bioassays on adults of Tribolium castaneum were conducted under laboratory conditions. The concentrations (0.1%, 0.5%, 1%) of the essential oils were tested to determine the LC 50 and TL 50 values. The results of the toxic by inhalation bioassay indicate that the four essential oils tested are toxic, causing 100% mortality on Tribolium castaneum adults after 24 hours of exposure to the 1% concentration. Peppermint essential oil showed a high toxic effect compared to other oils with a TL50 of 1.67H followed by lemongrass, basil and clove with TL50 values of 3.46; 3.95 and 4.98 H respectively. The essential oil at1% contact test shows that lemongrass has no toxic effect. On the other hand, peppermint caused a remarkable toxic effect on Tribolium castaneum (TL50 = 2.83 H), the effect was much less significant in cloves and basil with a TL 50 of 73 H for both. During 50 Hours of observing the repellent effect of the oils tested, the effect of peppermint was the most stable at an effectiveness rate close to 100%. Regarding ZNO, these nanoparticles do not improve the pesticidal effect when added to essential oils. Therefore, peppermint essential oil can be used as a pesticide to reduce losses caused by insect pests in stored foods.
Keywords: essential oils; Tribolium castaneum; inhalation; mortality; CL50; TL50.; زيوت أساسية ، الإستنشاق، موت الحشرات